Como se apresenta o cotidiano de idosos em instituições de longa permanência: uma revisão sistemática da literatura - AUGUSTO, Fernanda Luciana Monteiro (2023)
With the increase in the rate of aging combined with the gradual decrease in the family's ability to provide the necessary care to its older members, there appears to be an increase in the demand of people for long-term care institutions for the elderly (ILPI). Objective: Understand how the daily life of elderly people institutionalized in long-term institutions is presented. Method: A systematic review of the literature was performed, from August 2017 to November 2018, from the electronic databases Scientific Electronic Library Online (SciELO); Latin American and Caribbean Literature in Health Sciences (LILACS); National Library of Medicine (PubMed) and Medical Literature Analysis and Retrieval System Online (MEDLINE), considering the intermissionin years from 2008 to 2018. Results: After the entire process of selection and application of the admissibility criteria, 23 articles were included in this systematic review. The studies pointed out that the elderly in the context of institutionalization are dependent for the Daily Life Activities (ADL) and Instrumental Activities of Daily Living (IADL), being the greater functional impairment and predominating the female gender. The increase of the age, the time of institutionalization and the chronic diseases were related to greater dependence on the engagement in daily activities. Conclusion: Based on this review, it was possible to highlight the growing number of elderly people who, due to diverse demands, live in long-term care facilities, associated to other factors such as: high incidence of chronic diseases in this population, and away from their homes and significant people, have a negative impact on their daily lives, being evidenced damages in the performance of daily activities and the need for third-party assistance to carry them out.